2015
DOI: 10.1155/2015/572626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Salts Compounds on Mycelial Growth, Sporulation, and Spore Germination of Six Isolates ofBotrytis cinereain the Western North of Algeria

Abstract: Six isolates of Botrytis cinerea were isolated from leaves and stems of different tomato varieties taken from four areas in the northwest of Algeria where tomato is mostly grown in greenhouses and high tunnels. The purpose of this research was to determine the effect of two salts, NaCl and CaCl2, on three stages of Botrytis cinerea's life cycle. All isolates tested were stimulated in 50 to 150 ppm; NaCl was the most effective treatment to increase mycelial growth at two tested concentrations. However, at 300 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 46 publications
6
27
1
Order By: Relevance
“…In the composition of SR, YG, and Vogel salt solutions is observed the presence of MgSO 4 and KH 2 PO 4 , which can have influenced negatively the fungal development. Boumaaza, Benkhelifa, and Belkhoudja () demonstrated that the development of Botrytis cinerea can be affected positively or negatively by salt compounds according to the used concentrations. The possible use of water as a moistening agent for enzyme production can reduce the costs of the process because some specific salts are not required for maximal enzyme production.…”
Section: Discussionmentioning
confidence: 99%
“…In the composition of SR, YG, and Vogel salt solutions is observed the presence of MgSO 4 and KH 2 PO 4 , which can have influenced negatively the fungal development. Boumaaza, Benkhelifa, and Belkhoudja () demonstrated that the development of Botrytis cinerea can be affected positively or negatively by salt compounds according to the used concentrations. The possible use of water as a moistening agent for enzyme production can reduce the costs of the process because some specific salts are not required for maximal enzyme production.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) (in the dark) accelerate fungal growth as nutrient which was also suggested by already mentioned decrease in antifungal properties in the dark. There is partial evidence from the literature of significant influence of NaCl and CaCl 2 on the fungal growth [45].…”
Section: Purified Titania Samples (A-200 R Na -200)mentioning
confidence: 99%
“…Much worse activity of anatase than rutile under irradiation and in the dark could be caused by sodium presence, similarly as was proposed for alkali washed rutile sample (R Na -200), i.e., enhanced recombination of charge carriers and nutrient promoted fungal growth, respectively. According to recent studies of Boumaaza et al [45] sodium presence in various concentrations can promote or reduce the in vitro mycelial growth and sporulation. In contradistinction to P. chrysogenum, P25-200 exhibited the highest antifungal properties under irradiation against A. melleus.…”
Section: Experiments For Penicillum Chrysogenum and Apergillus Melleusmentioning
confidence: 99%
“…We tried to minimize this problem by using electrolyzed water products, as NaCl was the only compound added. At low concentrations, NaCl promoted growth of Botrytis cinerea (Boumaaza et al, 2015), but at high concentrations reduced growth of both B. cinerea (Boumaaza et al, 2015) and bread spoilers Penicillium roqueforti and Aspergillus niger (Samapundo et al, 2010). At concentrations up to 500 ppm, NaCl did not alter fungal growth for five species (Fig.…”
Section: Discussionmentioning
confidence: 90%